Processamento de carbonato de cálcio para aplicação nas indústrias de papel e de plástico - Felipe Ventura Oliveira (2005)
This work presents the experimental results for precipitated calcium carbonate (PCC) synthesis over a ground calcium carbonate (GCC) substrate. The parameters [Ca]/[CO3]T initial ratio, aqueous synthesis solution temperature, pH and coagulant concentration (EDTA) were investigated. The samples were characterized by scanningelectron microscopy (SEM), total carbon (TOC), specific surface area (BET method), particle size distribution and visible light reflectance (to measure the brightness of the samples). The results were compared with values from standard samples used in the paper industry.Initially, GCC was ground and classified to <10.0m. CaO was obtained by calcination of the GCC. The experimental procedure consisted in weighing 1.0g of GCC and the corresponding amount of CaO to obtain the desired [Ca]/[CO3]T initial ratio. CaO particles were hydrated with 500ml of distilled water and GCC was added to this pulp. The resulting pulp had its pH value adjusted with H2SO4 0.1M and was sent to theexperimental unit and kept under constant stirring. CO2 and EDTA were added to the pulp at the same time. The gas flux was stopped exactly 20 minutes later. The product was filtered, dried and analyzed.According to the experimental results, it was noted that an increase in the EDTA amount added to the pulp favored PCC homo-coagulation and also increased the size of the coagulum. PCC tends to homo-coagulate between pH 10 and 11, while it tends to precipitate over GCC particles between pH 8 and 9. It was also observed a decreasing of the material density. Particles size distribution did not meet the paper and plastics industries specifications, although it is not far from those specifications ofthe standard samples used in this work. Values found for specific surface area can be considered acceptable by those industries. Brightness analyses results showed that the average reflectance is 81.8%, while standard samples have presented a value of 95.0%, which means that the material did not fit paper industries specifications